TNF ?, LVH, Prehypertension, Abdominal obesity - Frans Wantania; Lucia Panda; Reggy L. Lefrandt (Jurnal Kardiologi Indonesia, 2013)
Introduction : Left Ventricular Hypertrophy (LVH) as an independentpredictor of mortality may develop in non diabetes obese. There’s a roleof inflammation because adipose tissue release the proinflammatory cytokinessuch as TNF ?. It is important to prove this inflammatory state andits impact to the healthy obese for preventing cardiovascular events in thefuture. Purpose of this study is to investigate correlation of TNF ? levelwith LVH and Prehypertension in non diabetes abdominal obesity.Methods : Eighty-two male abdominal obesity and non abdominal obesitysubjects with no history of diabetes were recruited in this cross-sectionalstudy. Tumor Necrosis Factor Alpha level were measured with radioimmunoassay,blood pressure measurement was taken 2 times. Left VentricularMass Index(LVMI) were evaluated by M-Mode and two dimensionechocardiogram and value above 115 g/m2 are indicative of LVH.Result : TNFa alpha level is higher in abdominal obesity group as compareto non abdominal obesity (0,7133+0,2072 pg/ml vs 2,395+1,5371 pg/ml,p<0,001). Most of obese subjects developed prehypertension. Subjectswith prehypertension showed higher plasma TNF alpha level as compare tosubject with normal blood pressure (2,83+1,649 pg/ml vs 1,38 + 0,3245pg/ml, p<0,001). We also found the LVH in 30 (60%) of abdominal obesitysubjects. Obese subject had larger LVMI than non obese (138,427+47,461g/m2 vs 90,188+16,06 g/m2, p<0,001), and correlates positively to plasmaTNF alpha level (r=0,727, p,<0,001).Conclusion : High level of plasma TNF alpha is associated with left ventricularhypertrophy and prehypertension in non diabetes male abdominalobesity.